„Nodo” kao samodovoljna alatka medijske etike!? - Donev, Dejan (NVO Civilni forum Nikšić, 2011)
From the concept of social responsibility, calling for a voluntary agreement not to do certain things in society (selfrestraint), it follows the possibility of self-regulation and practice of journalistic responsibility to publicly spoken word. In this context, self-regulation as a tool of media ethics, is a firm commitment of media professionals who care about the quality of their work to maintain a dialogue with the public. Promoting standards, self-regulation helps maintain the credibility of media among the public. This is particularly welcome in the new democracies, in which most of the independent press in itself new. Media selfregulation helps to reassure the public that free media are not without responsibility.
„Nodo” as a self-enough tool of media ethics!?
Keywords: social responsibility, media ethics, media selfregulation, ethical norms